2018
DOI: 10.1016/j.ajme.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pre-hypertension and hypertension and its related risk factors among undergraduate students in a Tertiary institution, Ghana

Abstract: Methods: This cross-sectional study was conducted among a total of 540 students. Participants were interviewed using questionnaires and their blood pressures (BP), height, weight were measured and Body Mass Index 'BMI' and Waist-to-Height Ratio (WHtR) were calculated. Repeated measurements were obtained on two successive times in students with persistently elevated BP. Data obtained was entered and analyzed using SPSS version 23. Final prevalence was adjusted for loss-to-follow up on participants with first el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 27 publications
2
25
1
2
Order By: Relevance
“…This current study on SHS students reveals a high prevalence of hypertension on the future generation of Ghana, with almost 40% with pre-HTN and a little over 5% with stages 1 and 2 HTN. This corresponds to the already existed literature of a 26.1% prevalence of pre-HTN in students of the Kwame Nkrumah University of Science and Technology (KNUST) 17. Although their study may differ a bit by the age range of their sample, it depicts a future speedy increase of the disease among indigenes of this country if measures are not put in place.…”
Section: Discussionsupporting
confidence: 74%
“…This current study on SHS students reveals a high prevalence of hypertension on the future generation of Ghana, with almost 40% with pre-HTN and a little over 5% with stages 1 and 2 HTN. This corresponds to the already existed literature of a 26.1% prevalence of pre-HTN in students of the Kwame Nkrumah University of Science and Technology (KNUST) 17. Although their study may differ a bit by the age range of their sample, it depicts a future speedy increase of the disease among indigenes of this country if measures are not put in place.…”
Section: Discussionsupporting
confidence: 74%
“…A recent systematic review has reported a paucity of data on cardiometabolic risk factors among the adolescent overweight/obese population in sub-Sahara Africa [50]. Some studies in Ghana have reported pre-hypertension (elevated blood pressure) and hypertension prevalence of 28.3, 36.3 and 39.2% among some adolescent and youth populations [31,56,57], which were less than what we are reporting. The high prevalence we reported could have resulted from "white coat" effect [58], as our study was conducted in a clinic setting.…”
Section: Discussioncontrasting
confidence: 69%
“…market men and women). The majority of the studies (62.4%) involved the general population while two (2.4%) conducted were among tertiary-level students [ 57 , 90 ].…”
Section: Resultsmentioning
confidence: 99%